IMPLEMENTATION OF CERDIK BEHAVIOR FOR BLOOD PRESSURE CONTROL AT PETERONGAN HEALTH CENTER - Rahmawati, Eli; Widyowati, Agustin; Elina, Agusta Dian (Journal of Indonesian Public Health Service, 2025)
Hypertension is a condition where blood pressure is high. The majority of cases suffering from hypertension are the elderly, so behavior is needed to control blood pressure, one of which is CERDIK behavior. CERDIK behavior consists of several lifestyles to improve and control health. So, this research aims to find out how CERDIK is implemented in efforts to control blood pressure at the Peterongan Community Health Center. This community service was conducted in the village of Kandangan Kepuhkembeng, Jombang Regency, with a sample size of 70 respondents. This research was conducted using interview techniques and observation, with the inclusion criteria of respondents with high blood pressure above 140 mmHg for systolic and diastolic pressure above 100 mmHg. This research was carried out by providing counseling and questionnaires about CERDIK Behavior, then, after that, a posttest was carried out with the results that the majority of respondents showed improvement, with 19 participants achieving good outcomes. It is hoped that the suggestions will increase public knowledge about the importance of implementing CERDIK behavior as a form of controlling blood pressure in hypertensive patients.